Flower-like triboelectric nanogenerator for blue energy harvesting with six degrees of freedom. (March 2022) - Wen, Honggui; Yang, Peiyuan; Liu, Guanlin; Xu, Shuxing; Yao, Huilu; Li, Wangtao; Qu, Hang; Ding, Jiajun; Li, Jiayu; Wan, Lingyu
Abstract: Triboelectric nanogenerators (TENGs) have recently become some of the most promising harvesters of the immense energy stored in the constant motion of ocean waves. Since ocean waves are chaotic and irregular, a TENG suitable for multiple motions is highly desirable for blue energy harvesting. We designed and fabricated a flower-like TENG (FL-TENG) for kinetic energy harvesting with six degrees of freedom. It consisted of six flower-petal sub-TENGs and two flower-core sub-TENGs that worked in the contact-separation mode. The FL-TENG converted kinetic energy into electric energy with the "flowering" and "folding" motions triggered by water waves. The petals of the FL-TENG mainly collected kinetic energy with two degrees of freedom for horizontal motion and with three degrees of freedom for rotational motion, and the cores of the TENGs harvested translational kinetic energy with one degree of freedom in the vertical direction. The FL-TENG demonstrated excellent power generation performance for different motion triggers. In various water wave environments, the FL-TENG efficiently collected kinetic energies with different degrees of freedom. Triggered by a water wave frequency of about 1.3 Hz and a wave height near 8 cm, the FL-TENG charged a capacitor of 220 μF to a voltage of 1.3 V in 1 min, supplying power to a watch, a calculator, and a hygrometer. It had robust functionality efficiency for various waves and it showed promising applications in developing self-powered smart marine sensors and distributed power systems in oceans. Graphical Abstract: A flower-like triboelectric nanogenerator (FL-TENG) harvests kinetic energy of motions with six degrees of freedom (DOF). FL-TENG accommodates various kinds of motion, including the horizontal and vertical translations, rotating motions, and swing, and shows robust power generation performances under different motion triggers. It is suitable for variable and complex wave motions and being promising for applications in blue energy harvesting. ga1 Highlights: A FL-TENG which is self-flowering and folding under triggered by motions was proposed. It harvests kinetic energy of motions with six degrees of freedom. It accommodates various motions such as translation, rotation and swing. The robust performance in water waves is promising for blue energy harvesting.